2019 IEEE Intelligent Vehicles Symposium (IV) 2019
DOI: 10.1109/ivs.2019.8813846
|View full text |Cite
|
Sign up to set email alerts
|

Evidential deep learning for arbitrary LIDAR object classification in the context of autonomous driving

Abstract: In traditional LIDAR processing pipelines, a point-cloud is split into clusters, or objects, which are classified afterwards. This supposes that all the objects obtained by clustering belong to one of the classes that the classifier can recognize, which is hard to guarantee in practice. We thus propose an evidential end-to-end deep neural network to classify LIDAR objects. The system is capable of classifying ambiguous and incoherent objects as unknown, while only having been trained on vehicles and vulnerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…There are also content layer corner case detection methods on LiDAR data, such as Wong et al [26], who introduce an open-set instance segmentation network on point clouds that identifies unknown points in an embedding space and groups them into unknown instances. Capellier et al [27] propose a method to detect both known and unknown objects in LiDAR data. Bolte et al [9] identify temporal layer corner cases for the camera sensor if the residual error between the real and a predicted image, weighted by the criticality of the location in the image, exceeds a threshold.…”
Section: Corner Case Detection Techniquesmentioning
confidence: 99%
“…There are also content layer corner case detection methods on LiDAR data, such as Wong et al [26], who introduce an open-set instance segmentation network on point clouds that identifies unknown points in an embedding space and groups them into unknown instances. Capellier et al [27] propose a method to detect both known and unknown objects in LiDAR data. Bolte et al [9] identify temporal layer corner cases for the camera sensor if the residual error between the real and a predicted image, weighted by the criticality of the location in the image, exceeds a threshold.…”
Section: Corner Case Detection Techniquesmentioning
confidence: 99%
“…We previously observed that using Instance‐Normalization (Ulyanov et al, 2016) in the final layer of the classifier would be an easy way to solve those problems (Capellier et al, 2019). Let υ ( x ) = ( υ 1 ( x ) , , υ d ( x ) ) be the mapping modeled by all the consecutive layers of the classifier but the last one; let true υ j ¯ be the mean value of the υ j function on the training set, and σ MathClass-open( υ j MathClass-close) 2 its corresponding variance.…”
Section: Generation Of Evidential Mass Functions From a Binary Glr Classifier Trained To Detect The Road In A Lidar Scanmentioning
confidence: 99%
“…Lidars provide a good physical description of the target and, due to that, lidars have been used for target detection, tracking, and motion prediction., Filtering of the ground and clustering of the target [ 102 , 103 , 104 , 105 ] are two methods widely used by lidar for object detection, which provide the spatial information of the target. To classify and recognize objects (like pedestrians, trees, or vehicles), lidars make use of techniques such as machine learning based on object recognition [ 106 , 107 , 108 , 109 ], and additional methods such as global and local extraction of features to help in providing the structure of the target. Lidar uses the Bayesian filtering framework and data association methods for target tracking and motion prediction to provide information, such as velocity, trajectory, and object positioning [ 110 , 111 , 112 ].…”
Section: Sensorsmentioning
confidence: 99%